2005
DOI: 10.1021/es048373d
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the Particulate Carbon Distribution from a Nonroad Diesel Generator

Abstract: The emissions of diesel particulate matter (DPM) from diesel engines are causing increasing health concerns due to their suspected carcinogenicity, especially the carbonaceous fractions. The total DPM emissions and the organic and elemental carbon (OC and EC) distributions of the DPM depend on many operating factors, such as load, engine design parameters, fuel sulfur content, fuel usage rate, and sampling conditions. Results of previous studies on the OC/EC variations with load for heavy-duty vehicles have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 10 publications
8
21
0
Order By: Relevance
“…For each excavator, the carbonaceous component (OM + EC) was the dominant species. This is consistent with results of a previous study by Liu et al (2005), who reported that the proportions of OC and EC in PM ranged from 70 to 91 % . Because the OC / EC ratio is also used to identify the source of atmospheric particulate pollution, further assessment was performed on these ratios in different operation modes for each excavator (Fig.…”
Section: Particulate Matter Composition For Individual Excavatorsupporting
confidence: 93%
See 2 more Smart Citations
“…For each excavator, the carbonaceous component (OM + EC) was the dominant species. This is consistent with results of a previous study by Liu et al (2005), who reported that the proportions of OC and EC in PM ranged from 70 to 91 % . Because the OC / EC ratio is also used to identify the source of atmospheric particulate pollution, further assessment was performed on these ratios in different operation modes for each excavator (Fig.…”
Section: Particulate Matter Composition For Individual Excavatorsupporting
confidence: 93%
“…The OC / EC ratio during idling was higher than 1 because soot is rarely generated at low temperatures and fuel-rich zones. These results are also consistent with those of Liu et al (2005). Furthermore, Liu et al (2005) reported that the OC / EC ratios decreased with an increase in load for non-road engines.…”
Section: Particulate Matter Composition For Individual Excavatorsupporting
confidence: 90%
See 1 more Smart Citation
“…The LSD particles contain a larger percentage of volatile substances than the ULSD particles. Liu et al (2005) suggested that higher fuel sulfur content results in higher concentration of nucleated sulfuric acid particles, which provides larger amount of sites for the condensation of volatile organic compounds. The size resolved particle volatility is compared among the three fuels in Fig.…”
Section: Mass-based Investigation Of Particle Volatilitymentioning
confidence: 99%
“…At 100% exhaust flow rate with a gas residence time of approximately 0.1 sec, the removal efficiency of the DPM mass increased from 69 to 83%, and the removal efficiency of the DPM number concentration increased from 67 to 86% when the engine load was reduced from 75 to 0 kW. The effect of decreasing engine power in turn led to a production of lower DPM mass and number concentrations, higher organic carbon (OC) and elemental carbon (EC) fractions, and higher gas-phase HC concentrations [37][38][39] were more pronounced than that of the residence time at a given condition. It is believed that a reduction of DPM mass and number loading to be treated inside the wESP and a change in OC/EC fraction may attenuate the effect of corona current suppression and allow the particles to impart charge more efficiently.…”
Section: Removal Of Dpm Mass and Number Concentrationsmentioning
confidence: 99%